Impact of Immunotherapy on Real-World Survival Outcomes in Metastatic Renal Cell Carcinoma - Poprach, Alexandr; Kiss, Igor; Stanik, Michal; Barusova, Tamara; Pospisilova, Lenka; Fiala, Ondrej; Kopecky, Jindrich; Richter, Igor; Melichar, Bohuslav; Studentova, Hana; Lakomy, Radek; Holanek, Milos; et al. (Targeted oncology, 2023)
BACKGROUND: Treatment options for metastatic renal cell carcinoma (mRCC) are rapidly expanding, and immunotherapy using checkpoint inhibitors is a first- or second-line option for most patients. OBJECTIVE: The objective of the present retrospective analysis was to explore the real-world impact of checkpoint inhibitor-based immunotherapy compared with therapy using other types of targeted therapies using a large real-world database. METHODS: RenIS, a registry of patients with mRCC was used as a data source. Outcomes were compared for cohorts treated with TKIs or mTOR inhibitors only [targeted therapy (TT) cohort] versus patients who received immunotherapy (IO) using a checkpoint inhibitor in any line of treatment (IO cohort). Data from a total of 1981 patients were extracted from the registry, including 1767 patients in the TT cohort and 214 patients in the IO cohort. RESULTS: The median overall survival from the initiation of first-line treatment was 24.5 months versus not reached (p < 0.001) in the TT cohort versus the IO cohort, respectively [HR 0.23, 95% CI (0.17-0.31), p < 0.001]. The probability of 5-year survival was 24.2 versus 67.9% in the TT cohort versus the IO cohort, respectively. Immunotherapy in any line of treatment was associated with a lower risk of death. Overall survival was superior for patients receiving immunotherapy as the first or second treatment line compared with patients treated with non-immunological targeted therapy. CONCLUSION: In real-world patients with mRCC, immunotherapy is associated with significant survival benefit. The present retrospective analysis shows the real-world benefit of second-line immunotherapy in patients previously treated with tyrosine-kinase inhibitors.
Keywords: nádory ledvin; karcinom z renálních buněk; Carcinoma, Renal Cell; protokoly protinádorové kombinované chemoterapie; retrospektivní studie; Humans; lidé; imunoterapie; Retrospective Studies; Immunotherapy; Kidney Neoplasms; Antineoplastic Combined Chemotherapy Protocols